La « civilizatio » du droit canonique: une problématique du droit québécois - Caparros, Ernest (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
Civilizatio means for the author the phenomenon of integration in the State Law of some rules of Canon Law, by opposition to the notion of Canonizatio, put out forward by V. del Giudice, illustrating the opposite operation, viz. the integration into Canon Law of rules of the State Law. The author illustrated this phenomenon of Civilizatio in the Civil Law of Québec, and more specificaly in relation to article 127 of the Québec Civil Code. The Despatie Case is taken as the dividing point of the article. In the first part (The Apogee of Civilizatio) the author underlines the extensive interpretation of article 127 that allows the courts to accept the religious impediments of marriage. This civilizatio, until 1921 went further; the Québec courts limited themselves to ratifying the decisions of the ecclesiastical tribunals. However, this civilizatio of the jurisprudence found a few opponents among the judges. The second part (The Decline of civilizatio) is dedicated to the study of the DespatieCase and its effect on Québec jurisprudence. This decision of the Privy Council has not been followed unanimously by the Québec courts. The author points out how some courts have followed the precedent reluctantly, while others have set the precedent aside explicitly or implicitly, for different reasons, one of those reasons being that the interpretation given by the Privy Council to article 127, reducing it to a mere matter of conscience, made it empty of any juridical sense. Nevertheless, in 1972 the Québec Court of Appeal laconically confirmed the decision of the Privy Council. This article, at the same time, explicitly illustrates the phenomenon of civilizatio, and implicitly illustrates the practice of certain jurisdictions which empowers the courts not only to interpret a legal provision, but also to alter its meaning.